Fenologia, produção e qualidade de frutos de variedades de caqui em região tropical brasileira - Nascimento, Lucas Marquezan (2015)
In recent years the Brazilian production of persimmon has expanded mainly due to the high yields that provides culture. Traditionally grown in temperate regions, the persimmon has been introduced in tropical regions. The cultivation in the State of Goiás would bring the advantage of reduction in post-harvest losses and offer fruit in the off season. Due to the lack of studies on the development of persimmon, the objective was to know the duration of phenological stages of five cultivars of persimmon and study production components, productivity and fruit quality of three persimmon cultivars conducted in tropical region. The work was conducted in the experimental area of the Rural Experimental Station of Anápolis, located in the city of Anápolis - GO, in a tropical climate with dry and rainy season well defined. Observations were made during a production cycle, crop 2014/2015, in the twelfth year of plant life. The cultivars evaluated in the first study were: Rama Forte, Giombo, Pomelo, Fuyu and IAC-5. Pruning was held on August 4, 2014, after the wintry rest of the plants, with subsequent application of hydrogen cyanamide 5%. Data were analyzed using descriptive statistics, mainly through the means of the variables analyzed. The growing cycle of crops starts on average 19 days after pruning and application of hydrogen cyanamide. The flowering lasts an average of ten days. The cycle until the harvest the last fruit took on average 233 days. There is variation in the duration of phenological stages and the cycle of cultivars, although all have received the same treatment. Pomelo and Rama Forte are the earliest cultivars, with the lowest cycle (183 days). Fuyu is the latest cultivar to produce (199 days). Giombo and IAC-5 have an average cycle of 191 days. In another experiment, the experimental design was completely randomized with eight repetitions of one plant per plot and three varieties of persimmon: Pomelo, Guiombo and Rama Fort. In the second part the design was completely randomized in a factorial 3 x 2, with three cultivars and two harvest seasons (190 DAP and 220 DAP), with four replicates of two fruits per plot (48 fruits). The results were submitted to analysis of variance (F test). The effects of the treatments were compared by Tukey test at 5% probability. Giombo was the most productive in an average of 545 fruits per plant, but with reduced mass (127 g), smaller and less attractive. Pomelo has the fruit with greater mass (224 g) even without the maximum production. No influence of harvest time on fruit parameters. Fruits harvested 190 days after pruning had higher SS content and lower acidity compared to fruits harvested at 220 days, regardless of the cultivar. The fruits of the plant darkened over time. All evaluated fruits kept their shape and color characteristics inherent to cultivate correspondent should be prioritized when the choice is made based on plant production, without worrying about the format of features and fruit color.